The Role of Simile in Strengthening Vertical Axis of Imaginary in Shamloo Poetry - Fouladi, Alireza; Ashiri, Hossein; Shajari, Reza; Rastgofar, Seyed Mohammad (Journal of History Culture and Art Research, 2017)
The styles change and literary technique (the techniques that create forms in literature) have an overlap with each other. According to that technique change will result in the evolution of style and vice versa. Technique structure also changed in modern poetry, according to the change in the structure and content of the lyrics has created against the traditional poetry. Unlike traditional poetry, which suffered from a disruption in the structure, the structure of modern poetry is organic. The techniques have changed to strength the organic structure and the imaginary vertical axis of poetry. Simile that has been applied as a widely used technique in literature, also structurally changed. The traditional compressed imagery exchanged with extended simile and this technique has created an important role in creating an organic structure. Application of this technique in Shamloo poetry differs his poetry among other modern poems. In Shamloo poetry, the structure of well-known similes’ of Persian poetry has exchanged in some cases. And in some cases this exchange has resulted to new structures of simile. Shamloo has used widely this technique in poetry. This paper reviews Shamloo similes of poetry and clarifies the role of this figure of speech in creating organic structure in Shamloo poetry.